1986
DOI: 10.1182/blood.v67.6.1600.bloodjournal6761600
|View full text |Cite
|
Sign up to set email alerts
|

Lymphocyte subsets in normal bone marrow

Abstract: Bone marrow aspirates and biopsies from ten normal donors were stained directly with monoclonal antibodies specific for lymphocyte, monocyte, and myeloid antigens, and were analyzed by flow cytometry. To avoid cell loss, lymphocytes were not specifically isolated prior to staining. T cells comprised 46% of aspirate lymphocytes and 22% of biopsy lymphocytes. Further, the Leu-3:Leu-2 ratio of bone marrow T cells was below 1.0. B cells comprised 8% to 11% of bone marrow lymphocytes in both aspirates and biopsies,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
9
0
1

Year Published

1994
1994
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 0 publications
2
9
0
1
Order By: Relevance
“…Our result is in line with reports that in healthy individuals, the bone marrow contains a lower percentage of CD3 + T lymphocytes compared with peripheral blood 11 . However, in contrast to the observations that healthy individuals contain comparable frequency of CD8 T cells among lymphocytes within the two anatomical locations 11 , our data demonstrate a diminishment of the CD8 T-cell subset in bone marrow of AML patients, suggesting a suppressed anti-leukemia CD8 activity in the marrow. Our further phenotypic analysis of T cells derived from AML patients showed that the majority of CD8 T cells in bone marrow are effector memory T cells (T EM ), and the percentage of T EM in bone marrow is significantly higher than that of peripheral blood (Fig.…”
supporting
confidence: 94%
“…Our result is in line with reports that in healthy individuals, the bone marrow contains a lower percentage of CD3 + T lymphocytes compared with peripheral blood 11 . However, in contrast to the observations that healthy individuals contain comparable frequency of CD8 T cells among lymphocytes within the two anatomical locations 11 , our data demonstrate a diminishment of the CD8 T-cell subset in bone marrow of AML patients, suggesting a suppressed anti-leukemia CD8 activity in the marrow. Our further phenotypic analysis of T cells derived from AML patients showed that the majority of CD8 T cells in bone marrow are effector memory T cells (T EM ), and the percentage of T EM in bone marrow is significantly higher than that of peripheral blood (Fig.…”
supporting
confidence: 94%
“…Currently, there is limited data available regarding the proportion of NK cells in normal bone marrow [2.7–4.8% in cardiac patients, 6–10% in normal paid donors]. The control bone marrows studied here had a higher median percentage and range of NK cells, which may in part be due to the fact that the bone marrows in this study were from patients with malignant neoplasms at some other site.…”
Section: Discussionmentioning
confidence: 73%
“…The persistence of antibody levels for life has been well-documented in humans ( 22 , 23 ). Indeed, work performed in the late 1980's showed that the BM is a site of B cell development from precursor cells as well as for antibody-secreting cells ( 24 – 26 ). However, whether this is due to the longevity of LLPCs that are generated at the time of vaccination/disease or to spontaneous differentiation of antigen-specific memory B cells into “new” LLPCs is more difficult to address.…”
Section: Long-lived Plasma Cells: a Brief Comparison Between Mice Andmentioning
confidence: 99%